Overcoming Multidrug Resistance in Salmonella spp. Isolates Obtained From the Swine Food Chain by Using Essential Oils: An in vitro Study - Lauteri, Carlotta; Maggio, Francesca; Serio, Annalisa; Festino, Anna Rita; Paparella, Antonello; Vergara, Alberto (Frontiers in Microbiology, 2022)
Antimicrobial resistance (AMR) is a global concern, and new approaches are needed to circumvent animal and food-borne resistant pathogens. Among the new strategies, the combination of antibiotics with natural compounds such as essential oils (EOs) could be an alternative to challenge bacterial resistance. The present study evaluates the phenotypic and genotypic antibiotic resistance of 36 Salmonella enterica (16 S. Typhimurium, 3 monophasic variant S. Typhimurium, 8 S. Enteritidis, 6 S. Rissen, 1 S. Typhi, and 2 S. Derby) strains, isolated from the swine production chain. The isolates displayed phenotypic resistance to gentamicin, amikacin, tobramycin, and tetracycline, while the resistance genes most commonly detected were parC, catA, nfsB, nfsA, blaTEM, tetA, and tetB. Then 31/36 Salmonella isolates were chosen to evaluate resistance to tetracycline and Thymus vulgaris, Eugenia caryophyllata, and Corydothymus capitatus EOs by determining minimum inhibitory concentrations (MICs). Finally, the synergistic effect between tetracycline and each EOs was evaluated by the checkerboard method, calculating the fractional inhibitory concentration (FIC) index. Among the EOs, C. capitatus displayed the best bioactivity in terms of MICs, with the lowest values (0.31 and 0.625 μl/ml). On the contrary, the strains showed the ability to grow in the presence of the maximum concentration of tetracycline employed (256 μg/ml). While not displaying a real synergism according to the FIC index, the combination of tetracycline compounds and the three EOs resulted in a significant reduction in the MIC values to tetracycline (4 μg/ml), suggesting a restoration of the susceptibility to the antibiotic in Salmonella spp.